Double pylorus: two sides to one story. Issue 12 (7th November 2016) - Umar, Shifa; Bilal, Mohammad
Key Clinical Message: It is important to recognize that "congenital" double pylorus is a benign condition, so that extensive work‐up can be avoided. Also, endoscopists should be aware of the double pylorus and demonstrate extra caution during endoscopic retrograde cholangiopancreatography (ERCP). Abstract : It is important to recognize that "congenital" double pylorus is a benign condition, so that extensive work‐up can be avoided. Also, endoscopists should be aware of the double pylorus and demonstrate extra caution during endoscopic retrograde cholangiopancreatography (ERCP).